AUTOMATION OF HEALTHCARE APPLICATIONS BY INCORPORATION OF IT - Suyunova, Zamira (Innovative Development in Educational Activities, 2023)
The use of modern technologies in the public, business and healthcare sectors will be examined in this work. The styles of typical behavior of the various life segments indicated above tend to change as a result of recent technology breakthroughs which also negatively impact how these segments function. The technology provides mysterious ways in the realm of automation and shines light on particular sectors that call for acceptable and excellent services. By doing this, the effectiveness of the entire system that is put in place is improved in terms of credibility and accountability. A variety of documentations that are empirically applied in the field of IT are investigated to look into how the automation of the application areas is influenced by IT regarding the equation of responsibility. The investigation goes from the most basic types of transactions which entail lesser levels of automation to highly automated systems which include, among other things, technology that analyze biometric fingerprints. In the example, the accountable potential of IT automation is discussed for the various applications with the goal of examining the advantages of application automation while removing the potentials that are unaccountable and impede the functionality that may result from the use of the systems applications on the various fields. The necessity of striking a balance between the advantages of automated IT applications and the full automation process including any system that would tend to make applications less efficient or raise questions about accountability is emphasized frequently throughout this work.